2006
DOI: 10.4049/jimmunol.176.9.5153
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Personalities of the Chemokine Receptor CCR7 in Dendritic Cells

Abstract: CCR7 was described initially as a potent leukocyte chemotactic receptor that was later shown to be responsible of directing the migration of dendritic cells (DCs) to the lymph nodes where these cells play an important role in the initiation of the immune response. Recently, a variety of reports have indicated that, apart from chemotaxis, CCR7 controls the cytoarchitecture, the rate of endocytosis, the survival, the migratory speed, and the maturation of the DCs. Some of these functions of CCR7 and additional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
212
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(224 citation statements)
references
References 77 publications
10
212
0
2
Order By: Relevance
“…In addition, it was shown that elevations of intracellular calcium are not necessary for directional migration of mouse neutrophils [36]. However, a recent publication, dealing with the dissection of chemokine receptor transduced signaling pathways, showed clearly that, in human monocyte-derived DC, chemokineinduced migration through CCR7 depended on the MAPK pathways, especially on ERK1/2 activity, whereas signaling through the PI3Kc/PKB pathway was responsible for mediating anti-apoptotic effects but not chemotaxis [34,51,52]. Apart from that, by comparing the impact between CCR7 and CXCR4 engagement on mature DC, we found a close association between ERK activity, especially ERK-1 activity, and the outcome of a chemotactic response in human monocyte-derived DC [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that elevations of intracellular calcium are not necessary for directional migration of mouse neutrophils [36]. However, a recent publication, dealing with the dissection of chemokine receptor transduced signaling pathways, showed clearly that, in human monocyte-derived DC, chemokineinduced migration through CCR7 depended on the MAPK pathways, especially on ERK1/2 activity, whereas signaling through the PI3Kc/PKB pathway was responsible for mediating anti-apoptotic effects but not chemotaxis [34,51,52]. Apart from that, by comparing the impact between CCR7 and CXCR4 engagement on mature DC, we found a close association between ERK activity, especially ERK-1 activity, and the outcome of a chemotactic response in human monocyte-derived DC [33].…”
Section: Discussionmentioning
confidence: 99%
“…3B, we observed a 77 and 40% increase in mRNA expression in P-compared to saline-and Met-P-injected tumors, respectively. This upregulation of the CCR7 chemokine receptor responsible for lymph node homing (18) suggests that the presence of plasmidic CpG motifs induces dendritic cell activation and migration from the tumor to the lymph nodes. These findings are consistent with previous observations obtained after in vivo administration of different TLR ligands such as LPS, imiquimod or resiquimod, leading to the emigration of dendritic cells from the liver, intestine lamina propria or skin towards draining lymph nodes (19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…9 -12,19 Resident rDC probe their immediate environment (which may include the lumen of the nephron) 19 and capture self and nonself molecules, whether derived from within or outside the kidney, via phagocytosis, pinocytosis, and receptormediated endocytosis. 12,19 In response to the same "danger" signals that invoke innate immune responses, rDC also upregulate the expression of co-stimulatory molecules and CCR7 (the CCR for ligands, CCL19, and CCL21, expressed by stromal cells in T lymphocyte-rich areas of lymph nodes 86,87 ) and migrate to secondary lymphoid tissues bearing any molecules captured within the kidney (or generated within rDC) for processing and presentation to adaptive immune cells. 9,10,12,53 These mature rDC potently stimulate T lymphocyte proliferation 9 -12 and, depending on the nature of maturing stimuli, 61,62,88 presumably secrete cytokines that promote the differentiation of naive T lymphocytes toward specific T helper (Th) effectors such as Th1, Th2, or Th17 lymphocytes 89 (this has yet to be formally reported).…”
Section: Adaptive Immunitymentioning
confidence: 99%